The Phenomenon of the Social Sufism Movement in the Digital Age: Rebuttal of Sufism which is Considered as a Setback and Must Leave the World - Munandar, Siswoyo Aris (UIN Sulthan Thaha Saifuddin Jambi, 2023)
Most people define Sufism as a branch of knowledge in Islam that teaches about mystical things, eccentric things, strange things and superstitious things. In fact, Sufism is often regarded as a teaching that must leave the world and live in poverty. The author is interested in further researching, that. Sufism and tarekat are not only able to survive and make various kinds of adaptations and accommodations, but even develop more broadly. This research is a qualitative research using netnography method. This method uses a separate analysis technique offered, namely AMS (Cyber Media Analysis) which goes through 4 levels, namely: Media space level, media document level, media object level, experience level. This study uses the Instagram website as a field (research area), and accounts of TQNNews.com, Youtobe TQN News, TQNMart.com, Idrisiyyah.com and other media as the community. The results of this study, Sufism in the technology and digital era is able to utilize technology as a medium of da'wah and as an online business, so that Sufism has progressed where Sufism is able to deal with teenagers who are addicted to drugs.